Sensible shoes a story about the spiritual journey - Brown, Sharon Garlough (Downers Grove, Illinois : IVP Books, an imprint of InterVarsity Press, 2013)
"Follow the moving stories of four women as they are drawn into a spiritual formation journey at a retreat center: Hannah, a pastor who doesn't realize how exhausted she is. Meg, a widow and recent empty-nester who is haunted by her past. Mara, a woman who has experienced a lifetime of rejection and is now trying to navigate a difficult marriage. Charissa, a hard-working graduate student who wants to get things right"--Page 2 of cover.
Description based on print version record.
Keywords: Christian women -- Fiction; Spiritual retreats -- Fiction; Friendship -- Fiction; FICTION / Christian / General; Christian fiction; Christian fiction; Electronic books